Determinants of Purchase Intention: Product Quality, Brand Image, and Price Perception Towards the Purchase of Wuling Air EV Electric Cars in Indonesia - Ekhsan, Farza Wirawan; Nugraheni, Titi; Hermawati, Sri; Pujiati, Desi; Misdiyono, Misdiyono (Dinasti Publisher, 2025)
The purpose of this study is to analyze the factors that influence the intention to purchase the Wuling Air EV electric car in Indonesia. The data analysis method used is quantitative primary data. The data used in this study used a questionnaire instrument via Google Form from 100 respondents. The research data was processed using the SPSS Program application. The sampling method in this study was non-probability sampling with a purposive sampling technique. The results showed that product quality, brand image, and price perception influenced the purchase intention of the Wuling Air EV electric car in Indonesia.